The relationship between perceived corporate social responsibility, corporate image, perceived motivation for involvement in socially responsible practices and purchase intention - Nunes, M.; Duarte, A.P.; Neves, J. (XI Phd Meeting in Social and Organizational Psychology, 2015)
The exponential growth of research about the relationship between corporate social responsibility (CSR) reflects its added value as a result of positive associations between social behavior, organizational performance and relationships with stakeholders. According to an integrated management approach, the investments in CSR practices are a growing concern for organizations, being part of their business, development and growth strategy, supporting the achievement of a corporate image and favorable competitive advantage. The central aim of this study is to understand consumers’ perceptions about companies’ engagement in CSR practices. Although consumers represent a stakeholder group particularly susceptible to CSR initiatives, multiple authors report the lack of information about how CSR activities truly creates value for the consumer. Therefore, we intend to examine if consumers have a higher purchase intention of products from a company that shows a socially responsible corporate behavior, and how they assess and perceive that social action of the company as consistent or inconsistent with its actions, values and policies in other domains. The results, obtained from a sample of 210 subjects, are under analysis, and we expect to present the final conclusions at the meeting.